Green road is open: Economic pathway with a carbon price escalator - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
The paper develops the concept of "Economic Pathways" (EPs), which characterize theory-based scenarios for an economy that strives to achieve decarbonization by mid-century. The theoretical framework derives closed-from analytical solutions for consumption, innovation, emissions, and population. The EPs differ in the stringency of assumed policies and associated income and emission development. Unlike the well-known "Shared Socioeconomic Pathways", they allow important causalities between the economy and the environment to be included and significantly narrow the scope of likely future developments. The quantitative part serves to illustrate the long-term consequences of climate policy. I show that deep decarbonization only moderately delays economic development, but requires increasing escalation of the carbon price. Subsidies to the research sector support income development significantly. The paper argues that the adoption of more stringent climate policies becomes more likely as the phase-out of fossil fuels increases. The "Green Road" is not only feasible, but also attractive and realistic.
Keywords: Q43; O47; Q56; O41; 330; Climate policies; consumption growth; population growth; endogenous innovation; economic pathways